Simplified out-of-plane seismic behavior assessment of non-structural rocking walls - Lestuzzi, Pierino (Frontiers in Built Environment, 2023)
This paper provides a simplified tool for preliminary seismic assessment of the out-of-plane behavior of non-structural walls, such as unreinforced masonry partition walls, based on non-linear time-history analyses. The studies are performed using equivalent single-degree-of-freedom (SDOF) systems and trilinear hysteretic models. The out-of-plane stability is investigated through statistical assessment of computed non-linear displacement demand related to spectrum-compatible ground motions. The trilinear model developed by Doherty and Griffith is used in the investigations. This hysteretic model is based on a rigid body behavior assumption and its accuracy was extensively validated using experimental results. Four sets of 12 recorded earthquakes, slightly modified to match design response spectra of different soil conditions, were used as ground motions for the non-linear time-history analyses. Non-structural walls located at the ground level as well as in the upper floors were also examined. The obtained results show that the static stability criterion provides an accurate estimate of the seismic resistance of non-structural rocking walls (i.e. vertical cantilevers with rigid body behavior). According to that criterion the ground acceleration threshold corresponds to the product of the wall aspect ratio by the acceleration of gravity (g). Compared to non-linear results, the corresponding calculated limit ground acceleration is on the safe side. Moreover, considering floor response spectra, this approach may be easily extended to non-structural walls situated in the upper storeys.